PENGEMBANGAN PETA INTERAKTIF BATAS WILAYAH INDONESIA HINGGA LEVEL KABUPATEN/KOTA BERBASIS LARAVEL DAN LEAFLET.JS UNTUK VISUALISASI ADMINISTRATIF - Edi Suherlan; Aufa Dhia Ghaisani Suherlan; Febri Febri (Journal of Innovation And Future Technology, 2026)
The recent expansion of administrative regions in Indonesia to 38 provinces and 514 regencies/municipalities increases the demand for accurate and scalable visualization of administrative boundaries. However, many existing Web GIS applications remain limited in scope and are not designed to manage national-scale spatial data efficiently. This study aims to design and implement a lightweight and extensible Web GIS architecture for visualizing Indonesia’s administrative boundaries down to the regency/municipality level. The research employs a software engineering approach consisting of requirements analysis, system design, implementation, and functional testing using the black-box testing method. The system is developed using the Laravel framework for backend management and Leaflet.js for client-side map visualization, with GeoJSON as the primary spatial data format and OpenStreetMap as the basemap.The developed application successfully visualizes administrative boundaries for all 38 provinces and 514 regencies/municipalities with consistent thematic styling, interactive features, and automatic zoom-to-fit. A centralized controller mechanism ensures stable asynchronous loading of spatial layers. These results demonstrate that the proposed architecture is effective for national-scale administrative mapping and can serve as a practical foundation for further Web GIS development.